2022
DOI: 10.31635/ccschem.021.202101021
|View full text |Cite
|
Sign up to set email alerts
|

A Cathodic Electrochromic Material Based on Thick Perylene Bisimide Film with High Optical Contrast and High Stability

Abstract: Cathodic electrochromic materials realized by n-type doping of conducting polymers are scarce. Even with limited cases reported in the literature, long-term stability is an urgent problem to be solved. Herein, we report a high performance and stable cathodic electrochromic material, poly(Th-Cl-PBI), based on a perylene bisimide function core. Due to its high electropolymerization efficiency and low steric hindrance of thiophene groups, perylene bisimide, which generally does not dissolve and form film easily, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The results (Figure S13) revealed that for BthCz and AQCz, there was no Bth or AQ anion peak even though the concentration ratio was as high as 1:50. As for PBICz, when the concentration ratios of PBICz and DMC were up to 1:30 and 1:50, two new peaks attributed to the PBI anion appeared at 761 and 922 nm, 34 and the intensity of those were higher at a ratio of 1:50 (Figure S13d inset). The results above illustrated that the electron transfer from DMC to electrode materials is closely related to their energy difference, concentration ratio, and the competition between electrode materials and water/oxygen traps.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…The results (Figure S13) revealed that for BthCz and AQCz, there was no Bth or AQ anion peak even though the concentration ratio was as high as 1:50. As for PBICz, when the concentration ratios of PBICz and DMC were up to 1:30 and 1:50, two new peaks attributed to the PBI anion appeared at 761 and 922 nm, 34 and the intensity of those were higher at a ratio of 1:50 (Figure S13d inset). The results above illustrated that the electron transfer from DMC to electrode materials is closely related to their energy difference, concentration ratio, and the competition between electrode materials and water/oxygen traps.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…ECMs can be further classified into two categories, namely inorganic ECMs and organic ECMs. [32,33] Inorganic ECMs have been widely used since they possess better stability and mature processing techniques. Organic ECMs can achieve color changes throughout the full spectrum from UV to IR, while the color changes of inorganic ECMs typically only occur in the visible range.…”
Section: Electrochromic Materials (Ecms) For Display Applicationsmentioning
confidence: 99%
“…ECMs can be further classified into two categories, namely inorganic ECMs and organic ECMs [32,33] . Inorganic ECMs have been widely used since they possess better stability and mature processing techniques.…”
Section: Electrochromic Materials (Ecms) For Display Applicationsmentioning
confidence: 99%
“…22 Consequently, within the various conjugated organic polymeric and small molecule available, anodically colored materials are typically based on electron-rich polythiophenes, 23–25 polyaniline (PANI), 26–28 polypyrrole (PPy), 29–31 carbazole, 32,33 and triarylamine, 34,35 while cathodically colored materials are based on electron-deficient viologens 36–38 and rylenimide derivatives. 39–42…”
Section: Introductionmentioning
confidence: 99%
“…22 Consequently, within the various conjugated organic polymeric and small molecule available, anodically colored materials are typically based on electronrich polythiophenes, [23][24][25] polyaniline (PANI), [26][27][28] polypyrrole (PPy), [29][30][31] carbazole, 32,33 and triarylamine, 34,35 while cathodically colored materials are based on electron-deficient viologens [36][37][38] and rylenimide derivatives. [39][40][41][42] Self-assembly in organic conjugated materials can significantly influence their solubility, optical absorptivity, charge-transfer, and ion-transport properties. [43][44][45] For instance, planarization of the conjugated backbone can promote aggregation, leading to an improved absorption coefficient and charge-transfer.…”
Section: Introductionmentioning
confidence: 99%